Adaptive proportional–integral controller using OLE for process control for industrial applications. (19th September 2017) - Paz, Marco A; Ramirez-delReal, Tania A; Garibo, Suselle C; Araiza-Illan, Dejanira; DeLuna-Ortega, Carlos A; Aguilar-Justo, Marving O
This article presents an implementation of an adaptive control architecture, which provides the combined advantages of better dynamic performance compared to other conventional industrial controllers, and the use of widely available hardware in process industry. Adaptive control architecture uses proportional–integral action and dynamic computation of the controller's gains (self-tuning regulator), to maintain performance specifications, even in the presence of parametric disturbances. This architecture offers advantages over other advanced embedded control systems implemented on industrial programmable logic controllers and other hardware platforms. Implementation of controllers on industrial hardware platforms is possible through the Object Linking and Embedding (OLE) for process control communication standard. The implementation for an adaptive controller here proposed was evaluated through experiments using first-order and overdamped second-order systems emulated by hardware-in-the-loop, with a programmable automation controller. Performance of the adaptive controllers was compared to that of conventional proportional–integral controllers, and effectiveness of the former over the latter was demonstrated through the experiments carried out.